Little Leaf Disease and Pine Wood Nematodes Disrupt Anatomical and Physiological Traits of Pinus taeda at Subtropical Conditions in Southern Brazil - Souza, T.; Dobner, M.; Fermino, P. C.P.; da Silva, L. J.R. [UNESP]; Nascimento, G. S. (Pleiades Publishing, 2023)
Abstract: We studied the influence of little leaf disease and pine wood nematodes’ presence on Pinus taeda anatomical and physiological traits. Branches and leaves were collected in two stands of P. taeda with 16 and 21 years. We found disturbances on lamina thickness, lamina width, central cylinder area, xylem area (left and right), phloem area (left and right), adaxial chlorophyll parenchymal thickness, distance from vascular conduits to stomata sub-cavity (mean and total), resin duct diameter (left and right), lower resin duct diameter (mean and total), top resin channel diameter, abaxial stomatal distance, and abaxial distance between stomata rows in strong symptom with little leaf disease. In the strong symptom, we found exponential decrease on N, P, and K content, as well as, on photosynthetic rate, needles’ transpiration, chlorophyll a, chlorophyll b, and carotene. The little leaf disease and pine wood nematodes change the needles’ anatomy and physiology, tree nutrition, and needle pigment in Pinus taeda. The syndrome has the ability: (i) to reduce Pinus’ phenotypic plasticity, and (ii) to show high severity in adult trees across its geographic distribution. The disturbances on needles’ anatomy directly affected plant nutrition and photosynthetic dynamics.
Keywords: forest ecosystems, leaves anatomical and physiological parameters, leaves macronutrient contents, leaves pigments; little leaf disease symptoms